Sphingosine‐1‐phosphate‐enhanced Wnt5a promotes osteogenic differentiation in C3H10T1/2 cells. (14th August 2016) - Hashimoto, Yoko; Kobayashi, Mari; Matsuzaki, Etsuko; Higashi, Katsumasa; Takahashi‐Yanaga, Fumi; Takano, Aiko; Hirata, Masato; Nishimura, Fusanori
Abstract: In this study, we investigated the involvement of Wnt signaling in sphingosine‐1‐phosphate (S1P)‐enhanced osteogenic differentiation of C3H10T1/2 pluripotent stem cells. We found that S1P enhanced the expression of Wnt5a and low‐density lipoprotein receptor‐related protein 5 or 6 (LRP5/6) during osteogenic differentiation. Wnt5a‐neutralizing antibody inhibited S1P‐enhanced expression of LRP5/6 and alkaline phosphatase, which are essential for osteogenic differentiation. Conversely, S1P did not affect endogenous canonical Wnt signaling. Taken together, S1P‐enhanced Wnt5a promotes LRP5/6 expression, resulting in the trigger of osteogenic differentiation of C3H10T1/2 cells. These findings suggest a potential beneficial role for S1P in bone regeneration.